2019
DOI: 10.1103/physrevb.100.155139
|View full text |Cite
|
Sign up to set email alerts
|

Single-parameter scaling in the magnetoresistance of optimally doped La2xSrxCuO4

Abstract: We show that the recent magnetoresistance data on thin-film La2−xSrxCuO4 (LSCO) in strong magnetic fields (B) 1 obeys a single-parameter scaling of the form MR(B,, at which point the single-parameter scaling breaks down. The functional form of the MR is distinct from the simple quadratic-tolinear quadrature combination of temperature and magnetic field found in the optimally doped iron superconductor BaFe2(As1−xPx)2 2 . Further, low-temperature departure of the MR in LSCO from its high-temperature scaling law … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Indeed, it has already been reported that the MR of LSCO x = 0.19 from Ref. [11] does not obey the quadrature form [59]. Our own analysis of the Giraldo-Gallo data [11] -shown in Figure 5 in the Supplementary Information -reveals that the MR more closely follows H{T 2 scaling.…”
Section: Mr Scaling Outside Of the Strange Metal Regimementioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, it has already been reported that the MR of LSCO x = 0.19 from Ref. [11] does not obey the quadrature form [59]. Our own analysis of the Giraldo-Gallo data [11] -shown in Figure 5 in the Supplementary Information -reveals that the MR more closely follows H{T 2 scaling.…”
Section: Mr Scaling Outside Of the Strange Metal Regimementioning
confidence: 60%
“…the LMR did not appear to obey the H{T quadrature scaling form [59]. (iii) What happens beyond the SC dome?…”
Section: Introductionmentioning
confidence: 99%
“…x h " βµ 0 H{T , where β " γµ B {αk B and thus ∆ρpT, xq " αk B T a 1 `x2 h. This implies that the timescale associated with the field (1{ω c ) plays a similar role to the thermal time τ h (" h k B T ) in this state (though we stress here that ω c is not necessarily associated with cyclotron motion). Starting from generalities of thermal quantum field theory, it is unclear why this should be the case [32], and even within a more conventional effective medium approach, such 'Planckian quadrature' behavior requires significant fine tuning of parameters [33,34]. Nevertheless, similar behavior has now been reported in both the electrondoped cuprates [12] and in FeSe 1´x S x [14] at or near their putative QCPs, suggesting that it is in fact a generic feature of quantum critical metals.…”
mentioning
confidence: 96%
“…[29]) reveals that, just as the T -linear ρ ab pT q persists over a wide doping range beyond p ˚ [2], so too does the anomalous linear MR. In LSCO, the MR at p " p ˚does not follow the quadrature form [34]. The different behaviour in LSCO might be due to the presence of the pseudogap, though clearly more measurements across p ˚are required to establish the role of the pseudogap in causing a breakdown in H{T scaling.…”
mentioning
confidence: 99%
“…Realistic theoretical explanations for this behavior thus far fall into two categories. The first, based on random resistor networks [26,27], attributes QLMR to the presence of disorder, either through real space binary distributions [28], real space patches [29], or doping inhomogeneity [30]. The second is intrinsic and driven by cyclotron orbits in combination with nesting fluctuations or peaks in the density of states arising through hot spots [31], turning points [32], magnetic breakdown [33] or van Hove singularities [34].…”
Section: Introductionmentioning
confidence: 99%